THE ROLE OF FAMILY VALUES IN THE DEVELOPMENT OF A CHILD'S PERSONALITY DURING PRESCHOOL AGE - Mo’minova Nargiza (Journals Park Publishing, 2022)
The family is a strong value for the development of every person, it plays an important role in the life of the state, in raising new generations, ensuring social stability and development.